Multilevel Resistive Switching in Hf-Based RRAM. (23rd April 2019) - Jain, Barsha; Huang, Chia-sheng; Misra, Durgamadhab; Tapily, Kandabara; Clark, Robert D.; Consiglio, Steven; Wajda, Cory S.; Leusink, Gert J.
Abstract : In this paper, the multilevel switching behaviors of resistive random-access memory (RRAM) devices with three different dielectric materials such as HfO2, HfZrO2 and HfAlO2 are investigated. We have further explored the switching characteristics with two different top electrode materials and with different processing environments. In all devices we have introduced a thin buffer layer to reduce switching power and improve the uniformity. Variation in the resistive behavior (Roff/Ron values) of different RRAM structures were observed and was correlated with possible oxygen vacancy related defects present in the dielectric.